Experimental and dft investigation on the corrosion inhibition behavior of expired drug lumerax on mild steel in hydrochloric acid - Dohare P.; Chauhan D.S.; Hammouti B.; Quraishi M.A. (My University, 2025)
The present work describes the application of expired drug Lumerax as corrosion inhibitor for mild steel (MS) in 1 M HCl after its expiry date using gravimetric measurements, electrochemical studies and surface analysis. The adsorption of Lumerax on MS surface obeys the Langmuir isotherm. And protection film confirmed by SEM and AFM. Impedance analysis showed that the presence of inhibitor considerably affects the charge transfer resistance and the double layer capacitance of MS surface. Potentiodynamic polarization shows that Lumerax behaves as a mixed type corrosion inhibitor.DFT calculations were used to evaluate the structural, electronic and reactivity parameters of the drug components (Artemether and Lumefantrine) and the theoretical investigation verifies the validity of the use of expired Lumerax drug as a novel and efficient corrosion inhibitor for mild steel. © 2017 by CEE (Center of Excellence in Electrochemistry).